2006
DOI: 10.2355/isijinternational.46.1251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Addition of P on the Mechanical Properties of Low Alloyed TRIP Steels

Abstract: IntroductionCommon TRIP-aided steels contain roughly 0.15 mass% C, 1.5 mass% Si and 1.5 mass% Mn. The high Si content in conventional CMnSi TRIP-aided steels is known to give rise to galvanizing problems and is also known to cause low ductility levels in the as-cast condition. Si is also known to increase the ductile-to-brittle transition temperature of ferritic steels. These are the main reasons to keep the Si content of TRIP-aided steels as low as possible. It is known that Al, in addition to being a strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 9 publications
(11 reference statements)
0
17
0
Order By: Relevance
“…28) Then, the so-called "new" ferrite has been usually considered as something "to be avoided" and therefore many authors have used in their studies very high cooling rates (Ͼ30°C/s) or even quenching to salt baths that hinder austenite transformation during cooling. 1,2,6,[9][10][11]19,24,29,30) However, TRIP steels are usually coated and those cooling rates are much higher than the typical values close to 15°C/s found in industrial continuous galvanizing (CG) lines. 7) There is controversy in the literature about the nature and properties of new ferrite as well as its influence on the stabilization of austenite and final mechanical properties of multiphase steels.…”
Section: The Role Of New Ferrite On Retained Austenite Stabilization mentioning
confidence: 99%
See 1 more Smart Citation
“…28) Then, the so-called "new" ferrite has been usually considered as something "to be avoided" and therefore many authors have used in their studies very high cooling rates (Ͼ30°C/s) or even quenching to salt baths that hinder austenite transformation during cooling. 1,2,6,[9][10][11]19,24,29,30) However, TRIP steels are usually coated and those cooling rates are much higher than the typical values close to 15°C/s found in industrial continuous galvanizing (CG) lines. 7) There is controversy in the literature about the nature and properties of new ferrite as well as its influence on the stabilization of austenite and final mechanical properties of multiphase steels.…”
Section: The Role Of New Ferrite On Retained Austenite Stabilization mentioning
confidence: 99%
“…On this matter, some authors found that Al can accelerate the bainite formation. 13,23,24) As a result, it has been suggested that TRIP steels with Al additions could be produced on a CGL without isothermal bainitic transformation section 8) or even through continuous cooling. 25) It is generally accepted that the cooling rate from the intercritical annealing (IA) to IH has to be fast enough to…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus is useful for solid solution strengthening 12,13) and P-TRIP steels have shown interesting microstructural characteristics and mechanical properties. 9,14) However, it has been shown that P additions slow galvannealing kinetics 15) and can lead to cold work embrittlement 16) for low C contents. According to some authors, Al as a solute element does not segregate to the surface during intercritical annealing before galvanizing, 17) so Al additions are not expected to influence the coatability adversely.…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve the austenite stabilization some authors have used CMnSi TRIP-aided steels with Si contents above 1.5 %. [5][6][7][8] However, in selecting steels for coated applications, it is important to pay attention to the silicon content, as high Si additions are known to cause galvanizing problems 9) and it is generally accepted that a level of Si above 0.5 % will hinder coating. 10) Concretely, Si forms a very strong and adherent layer of complex manganese-silicon-oxides, which is easily rolled into the surface during hot rolling and is difficult to be removed.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in the previous works these properties result from a synergic effect that combines the characteristics of ferrite, bainite and mechanically unstable retained austenite which partially transforms to martensite under strain [1,2,3,4]. Therefore, in order to obtain an accurate description of the microstructure-mechanical properties relation in TRIP-assisted steels, it is very important to know how the stress and strain (static or dynamic) distribute among the different microstructural constituents and how the microstructure responds to the external load.…”
Section: Introductionmentioning
confidence: 99%